A gestão democrática em uma escola de educação de jovens e adultos - Rosa, Camila Petrucci dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper addresses the democratic school management within the school organizations. For this, initially made brief remarks on labor relations, the development of administrative and organizational theories. Later, we reflect on how the se labor relations are organized in the educational environment and what education theoretical contributions to the development of school management in Brazil. Therefore, we discuss the Brazilian educational policies that postulate and legitimate democratic school management. Studies of everyday guided the theoretical basis of this work, we wonder what school subject dealing with the discourse of democratic and participative management. Forward the hypothesis that participatory management should be a prominent space in schools, the aim of this study was to investigate the school management of a municipal school of Youth and Adult Education, which brings in your organization pedagogical foundation and educational principles espoused by Paul Freire. The specific objectives of the study are: a) to investigate and describe how is the organization's management of school youth and adults; b) understand the role of managers; c) check how teachers and administrators understand the process of managing this school. From a methodological point of view the daily life of the studies led this work to procedures and qualitative analysis of ethnographic referring to practices that have occurred in adult education school along with the theoretical foundation. Participated in this research members of the school management group and four teachers of Youth and Adult Education rooms. The results obtained showed that dialogue and democracy go together, that the school is an organization with different world views, which need to be primarily present in the identity of the schools. It was also possible to find different democratic practices in the management and organization of the Educational Center that make school subjects become...

O presente trabalho aborda a gestão escolar democrática, dentro das organizações escolares. Para isso, inicialmente fizemos breves considerações sobre as relações de trabalho, o desenvolvimento das teorias administrativas e organizacionais. Posteriormente, refletimos sobre como essas relações de trabalho se organizam no ambiente educacional e quais as contribuições de teóricos da educação para o desenvolvimento da gestão escolar no Brasil. Neste sentido, abordamos as políticas educacionais brasileiras que postulam e legitimam a gestão escolar democrática. Os estudos do cotidiano nortearam o embasamento teórico deste trabalho, nos questionamos como os sujeitos escolares lidam com o discurso da gestão democrática e participativa. Frente à hipótese de que a gestão participativa deva ser um espaço de destaque no âmbito escolar, o objetivo geral deste trabalho foi investigar a gestão escolar de uma escola municipal de EJA, que traz em sua organização a fundamentação pedagógica e os princípios educativos defendidos por Paulo Freire. Os objetivos específicos do trabalho são: a) investigar e descrever como se dá a organização da gestão da escola de jovens e adultos; b) compreender o papel dos gestores, e; c) verificar como professores e gestores compreendem o processo de gestão desta escola. Do ponto de vista metodológico os estudos sobre o cotidiano levaram este trabalho para procedimentos e analises qualitativas de cunho etnográfico referindo as práticas ocorridas na escola de EJA juntamente com a fundamentação teórica. Participaram desta pesquisa os membros do grupo gestor da escola e quatro professoras de salas de EJA. Os resultados alcançados mostraram que o diálogo e a democracia andam juntos, que a escola é uma organização com diferentes visões de mundo, que precisam estar fundamentalmente presentes na identidade das instituições escolares. Foi possível ainda encontrar diferentes práticas...
Keywords: Educação - Estudo e ensino; Escolas - Organização e administração; Gestão democrática; Educação de adultos; Educação popular; Educação - Brasil - História; Education Study and teaching